Effect of the SAFiAl health program on the academic performance of high school students - Rodríguez Ramírez, Gabriela; Manuel Ortega Muñoz (Acta Universitaria, 2022)
Students’ academic performance is viewed as a synonym of productivity at school, which is expressed through grades and is determined by multiple factors, including health. This study aimed to determine the effect of the SAFiAl health program on high school students’ performance. This research adopted a quasi-experimental design, where a control group (n = 21) and an intervention group (n = 24) were included, and a pedagogical test was administered as pretest and posttest to both groups. The intervention consisted in the development of a health program conformed by eight sessions under the structure of an instructional design. The results indicate that, after the intervention, the academic performance value showed statistically significant differences between the experimental group (14.12 ± 2.60) and the control group (12.04 ± 4.06), with a value of p = 0.05. Therefore, it is concluded that the health program had a positive effect on high school students’ academic performance.